Survey on the Status of the Hospital Information Systems in Portugal - Lapão, L. Velez (Methods of Information in Medicine, 2007)
Objectives: To diagnose the hospital information systems’ situation in Portugal.Methods: Developing a survey on HIS department heads.Results: Several weaknesses were identified in most HIS departments, such as substantial lackof people and of qualifications to deal with HIS challenges. The Nolan and McFarlan Matrix helped assess the SNS IS maturity at stage 3, characterized by the generalized lackof IS integration.Conclusions: The results are very relevant to explain the many delays (and conflicts) in implementing HIS and therefore the actual status of HIS in Portugal. The most successful cases of HIS implementation were recognized as related to the existence of an active CIO. Complexity theory can further define guidelines for the development of HIS that help keep the navigation towards “smart healthcare”.
Keywords: Hospital information systems; hospital information systems management; survey; CIO; complexity